Filsafat Pendidikan Pragmatisme dan Konstruktivisme - Muryani Muryani; Anengsih; Sholeh Hidayat; Ratna Sari Dewi (Syntax Literate, 2023)
Pragmatism teaches that the purpose of thinking is the advancement of life, namely to advance and enrich life. According to pragmatism, the essence of reality is everything that is experienced by humans. He argues that the core of reality is the experience experienced by humans. This then becomes the cause that pragmatism pays more attention to things that are actual in nature so that it has implications for determining value and truth. Thus value and truth can be determined by looking at the reality that is happening on the ground and no longer looking at other factors such as sin or not.This is in line with what James said, The real world is the world of human experience. What is the focus of our education now. In general, nature becomes the central point of education; nature is the goal. Humans become "slaves" of nature; science, technology and pragmatic matters take the most important place. Human-centered education is getting sidelined. This cannot be separated from the most influential figure in the world of education, John Dewey. He was a figure in American education in the early and mid-20th century and promoted the concept of pragmatism. Dewey said that education is a growing personal adjustment to its environment (education is an "adjustment of the growing personality to its environment). It makes the environment the center of education. For Dewey, humans must be adapted to their environment without mentioning the definition of "environment" (environment). clearly".